The Political Argumentation in Hipacy Pociej’s Antirrēsis - Nosilia, Viviana (Poznańskie Studia Slawistyczne, 2016)
The article investigates the interconfessional polemical literature as a valuable source offering an insight into the major values of the society of the Polish-Lithuanian Commonwealth in the 16th–17th centuries. These texts also help understanding phenomena other than the merely religious ones. In the debate, juridical and political arguments were used too. We focus on the case study of Hipacy Pociej’s Antirrēsis (Ruthenian: 1599; Polish: 1600), written in response to Marcin Broniewski’s Apokrisis (1597). Pociej, who had an outstanding political career before becoming a Uniate bishop, mastered these arguments perfectly. His work is imbued with the mentality of the communitas nobilium, which also played a part in his lexical choices.